Uji Aktivitas Antioksidan dan Formulasi Gel Ekstrak Etanol Daun Jeruk Nipis (Citrus aurantifolia): Antioxidant Activity Test and Gel Formulation of Lime Leaf Ethanol Extract (Citrus aurantifolia) - Bayu Tri Andika; Dewi Rahmawati; Hadi Kuncoro (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Citrus aurantifolia leaves have several pharmacological properties such as antibacterial and antioxidant activity. The main objective of this study was to determine the antioxidant activity and obtain the best gel formula from the lime leaves ethanolic extracts. Five different concentrations of Citrus aurantifolia leaves extract namely FI, FII, FIII, FIV, and FV were tested for its antioxidant activity using the DPPH method. Furthermore, the lime leaves extract gel were formulated using carbopol 940. The gels were then evaluated for various parameters including organoleptic, homogeneity, pH, spreadability and viscosity to select best formulation. The extraction process was conducted using maceration method. The results of the DPPH radical scavenging activity showed that lime leaves extract with concentration 60,84 ppm has the preeminent IC50 value. The preparation of lime leaf ethanol extract gel obtained was clear white, clear green, green, brownish green, dark green, homogeneous, and had a characteristic smell of lime leaf. Evaluation of dispersion of 5-5.4 cm, pH of 5.1-5.8, and viscosity of 4.44-6.39 Pa.s. From the evaluation results, it can be concluded that formula 2 is the best formula.